Parkinson's disease with camptocormia. Issue 11 (5th June 2006) - Bloch, F; Houeto, J L; Tezenas du Montcel, S; Bonneville, F; Etchepare, F; Welter, M L; Rivaud-Pechoux, S; Hahn-Barma, V; Maisonobe, T; Behar, C; Lazennec, J Y; Kurys, E; et al.
Abstract : Background: Camptocormia is defined as an abnormal flexion of the trunk that appears when standing or walking and disappears in the supine position. The origin of the disorder is unknown, but it is usually attributed either to a primary or a secondary paravertebral muscle myopathy or a motor neurone disorder. Camptocormia is also observed in a minority of patients with parkinsonism. Objective: To characterise the clinical and electrophysiological features of camptocormia and parkinsonian symptoms in patients with Parkinson's disease and camptocormia compared with patients with Parkinson's disease without camptocormia. Methods: Patients with parkinsonism and camptocormia (excluding patients with multiple system atrophy) prospectively underwent a multidisciplinary clinical (neurological, neuropsychological, psychological, rheumatological) and neurophysiological (electromyogram, ocular movement recording) examination and were compared with age-matched patients with Parkinson's disease without camptocormia. Results: The camptocormia developed after 8.5 (SD 5.3) years of parkinsonism, responded poorly to levodopa treatment (20%) and displayed features consistent with axial dystonia. Patients with camptocormia were characterised by prominent levodopa-unresponsive axial symptoms (ie, axial rigidity, gait disorder and postural instability), along with a tendency for greater error in the antisaccade paradigm. Conclusion: We suggest that (1) the salient features of parkinsonism observed in patients with camptocormia are likely to represent a specific form of Parkinson's disease and camptocormia is an axial dystonia and (2) both camptocormia and parkinsonism in these patients might result from additional, non-dopaminergic neuronal dysfunction in the basal ganglia.